2018
DOI: 10.1590/1980-57642018dn12-010008
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Pentagon Drawing test for the screening of older adults with Alzheimer's dementia

Abstract: The Pentagon Drawing Test (PDT) is a common cognitive screening test.Objective: The aim of this study was to evaluate performance properties of a specific PDT scoring scale in older adults with Alzheimer's disease (AD) and healthy controls.Methods: A cross-sectional study of 390 elderly patients, aged 60 years or older with at least two years of education was conducted. All participants completed clinical and neuropsychological evaluations, including the Cambridge Cognitive Examination, the Mini-Mental State E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
(43 reference statements)
0
20
0
2
Order By: Relevance
“…Most of the studies found in this review compared the diagnostic accuracy of new instruments, such as the Rowland Universal Dementia Assessment Scale, or combinations of traditional screening instruments, with the accuracy of the MMSE. These studies have indicated that longer instruments, such as the Mattis Dementia Rating Scale and the Cambridge Cognition Examination, and shorter ones, such as the Cognitive Abilities Screening Instrument-Short Form, may be just as accurate in detecting AD in populations with little educat ion 3,20,21,22,25,36,37,38,39,40,41,42,43,44 . When combined with the MMSE, these instruments may increase the diagnostic accuracy 3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies found in this review compared the diagnostic accuracy of new instruments, such as the Rowland Universal Dementia Assessment Scale, or combinations of traditional screening instruments, with the accuracy of the MMSE. These studies have indicated that longer instruments, such as the Mattis Dementia Rating Scale and the Cambridge Cognition Examination, and shorter ones, such as the Cognitive Abilities Screening Instrument-Short Form, may be just as accurate in detecting AD in populations with little educat ion 3,20,21,22,25,36,37,38,39,40,41,42,43,44 . When combined with the MMSE, these instruments may increase the diagnostic accuracy 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The Bourke scale for scoring the Pentagon Drawing Test proved to be able to distinguish the control from the AD group, although its sensitivity was low. Applying the Bourke scoring scale for analysis of this subtest may contribute to the assessment of visuoconstruction in the MMSE that is not allowed by the usual binary scoring method 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, IPT is aimed to evaluate constructional apraxia (CA), which is defined as the inability to draw two or three‐dimensional objects using single dimension lines . It has already been recognized as valuable screening tool to identify subjects with Alzheimer disease and to predict inability to perform pulmonary function tests correctly …”
Section: Introductionmentioning
confidence: 99%